Low and variable pH decreases recruitment efficiency in populations of a temperate coral naturally present at a CO2 vent. (7th December 2018) - Caroselli, Erik; Gizzi, Francesca; Prada, Fiorella; Marchini, Chiara; Airi, Valentina; Kaandorp, Jaap; Falini, Giuseppe; Dubinsky, Zvy; Goffredo, Stefano
Abstract : Atmospheric carbon dioxide enrichment alters seawater carbonate chemistry, thus threatening calcifying organisms such as corals. Coral populations at carbon dioxide vents are natural acidification experiments that mimic organism responses to seawater pH values projected for 2100. Even if demographic traits are paramount information to assess ecological relationships and habitat suitability, population dynamics studies on corals thriving under acidified conditions are lacking. Here, we investigate the demography and reproduction of populations of the solitary, symbiotic, temperate coral Balanophyllia europaea naturally living along a pH gradient at a Mediterranean CO2 vent. Gametogenesis and larval production were unaffected while recruitment efficiency collapsed at low and variable pH, contributing to coral abundance decline and suggesting that life stages between larval release and early polyp growth are hindered by acidification. Exploring these processes is crucial to assess coral fate in the forthcoming acidified oceans, to preserve coral ecosystems and the socioeconomic services they provide.